2006
DOI: 10.1063/1.2193350
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of n-type GaPN grown by molecular-beam epitaxy

Abstract: We have investigated electrical properties of n-GaPN layers grown by molecular-beam epitaxy with an rf-plasma source using sulfur and tellurium as dopants. The electron concentration in n-GaPN was about 10 times lower than that in n-GaP. Desorption of dopants from the grown surface by impinging N atoms may be one of the possible causes for the reduced electron concentration. In addition, electron mobilities in GaPN were restricted by ionized impurity scattering even at room temperature (RT). N atoms at N-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…In spite of the fact that we used the same Si doping condition during the epitaxial growth, the shallow donor density decreased with increasing the N composition in the GaP 1−x N x layers. A similar reduction of electron concentration was reported by Furukawa et al 24 in the S and Te-doped GaP 1−x N x layers grown by rf-MBE. They suggest that such reduction of the carrier concentration could arise from the N-impinging desorption of the dopants from the surface during growth, or the electron capture by N-related deep levels.…”
Section: A Xps and Raman Characterizationsupporting
confidence: 69%
See 3 more Smart Citations
“…In spite of the fact that we used the same Si doping condition during the epitaxial growth, the shallow donor density decreased with increasing the N composition in the GaP 1−x N x layers. A similar reduction of electron concentration was reported by Furukawa et al 24 in the S and Te-doped GaP 1−x N x layers grown by rf-MBE. They suggest that such reduction of the carrier concentration could arise from the N-impinging desorption of the dopants from the surface during growth, or the electron capture by N-related deep levels.…”
Section: A Xps and Raman Characterizationsupporting
confidence: 69%
“…[29][30][31] No pronounced change in the activation energy of the Si donor was observed in the GaP 1−x N x alloys. Furukawa et al 24 also reported almost the same activation energy for the S dopant in GaP 1−x N x ͑x =0% − 1.9%͒.…”
Section: Tas Studymentioning
confidence: 83%
See 2 more Smart Citations
“…Ideally, the whole Si and III-V layers are grown by using the two-chamber MBE system. However, in this work, an LED structure was grown by the other conventional single-chamber MBE system, because doping conditions for n-and p-type GaPN layers have been already obtained [8] and an InGaPN/GaPN DH LED has been realized in the previous work with the single-chamber MBE system [7]. In the single-chamber MBE system, Ga, In and P 2 flux were supplied by evaporating metal Ga, metal In and InP polycrystals with conventional thermal effusion cells, respectively.…”
Section: Methodsmentioning
confidence: 99%